Survival Significance of Number of Positive Lymph Nodes in Oral Squamous Cell Carcinoma Stratified by p16 - Li, Peng; Fang, Qigen; Yang, Yanjie; Chen, Defeng; Du, Wei; Liu, Fei; Luo, Ruihua (Frontiers in Oncology, 2021)
Objectives: To analyze the significance of the number of positive lymph nodes in oral squamous cell carcinoma (SCC) stratified by p16. Methods: A total of 674 patients were retrospectively enrolled, and divided into 4 groups based on different number of positive lymph nodes (0 vs 1-2 vs 3-4 vs ≥5). The Kaplan-Meier method was used to calculate the disease-free survival (DFS) and disease-specific survival (DSS) rates. Cox model was used to evaluate the independent risk factor. Results: p16 showed positivity in 85 patients with a rate of 12.6%. In patients with p16 negativity, the 5-year DFS rates were 52%, 39%, and 21% in patients with 0, 1-2, and 3-4 positive lymph nodes, respectively, in patients with ≥5 positive lymph nodes, all patients developed recurrence within 2 years after operation, the difference was significant; the 5-year DSS rates were 60%, 38%, and 18% in patients with 0, 1-2, and 3-4 positive lymph nodes, respectively, in patients with ≥5 positive lymph nodes, all patients died within 4 years after operation. The difference was significant. In p16 positivity patients, the 3-year DFS rates were 41% and 17% in patients with 0-2 and ≥3 positive lymph nodes, respectively, the difference was significant; the 3-year DSS rates were 84% and 46% in patients with 0-2 and ≥3 positive lymph nodes, the difference was significant. Conclusions: The number of positive lymph nodes is significantly associated with the survival in oral SCC, its survival effect is not affected by p16 status.